FOOD AND FEEDING HABITS OF THE DEMERSAL FISHES OFF BOMBAY - Suseelan, C; Nair, K V Somasekharan (Indian Journal of Fisheries, 2011)
The food and feeding habits of some of the common fishes landed by the trawlersat Bombay have been studied by employing the points method and the volumetricmethod. Ilisfia filigera has been observed to be carnivorous, feeding chiefly on Acetesand teleosts, and Thrissocles malabarica feeds predominantly on planktonic organisms.The food of the catflshes consisted of benthic epifauna and infauna and also fishes. Polydactylusindicus and Polynemus heptadactylus were feed ing at all depths in the water column.Pomadasys hasta was noted to be mostly a benthic feeder. Pseudosciaena diacanthus,Otolithoides brunneus, Otolithus ruber, Johnius dussumieri, J. carutta, J. axillaris, J. aneusand Sciaena dussumieri fed chiefly on prawns, Acetes and fishes. Muraenesox talabonoideshas been found to be predacious mainly on fishes. The seasonal variation in thediet of the fishes as a whole was determined by finding out the 'food index'. Prawnsand teleosts were the most important food items consumed by the majority of the species.The values of the 'feeding index' did not show any significant variations in the differentmonths. However, it was slightly higher during the period July to September.